Historical and Ethymological Analysis of the Music Term "Kuy" (Zien Journal of Social Sciences and Humanities, 2022)
This article analyzes the historical and etymological features of the term melody, which is actively used in Uzbek music terminology today. The formation and development of the term is semantically and structurally interpreted and considered on the basis of sources. It has been scientifically explained that the etymology of the term melody is not related to the term blue, which means "poem, song", but to the root root, which is formed by combining tones.